Coinfection with hepatitis B and D: Epidemiology, prevalence and disease in patients in Northern California. Issue 9 (22nd August 2013) - Gish, Robert G; Yi, Debbie Hana; Kane, Steve; Clark, Margaret; Mangahas, Michael; Baqai, Sumbella; Winters, Mark A; Proudfoot, James; Glenn, Jeffrey S
Abstract: Background and Aims: With no report on the overall prevalence and ramifications of hepatitis Delta virus (HDV) infection in the United States for more than two decades, the characteristics of chronic hepatitis B virus (CHB) patients coinfected with HDV, including clinical presentation, rate of hepatitis C virus tri‐infection, and HDV viral load, were assessed. Methods: At California Pacific Medical Center, a retrospective chart review was conducted on all CHB patients. Results: Of 1191 CHB patients, 499 had been tested for HDV, with 42 (8%) determined to be coinfected; half of these were also hepatitis C virus‐infected. Cirrhosis was present in 73% of the coinfected, 80% of the tri‐infected, but only 22% of the monoinfected. Twenty‐nine patients (69%) were Caucasian non‐Hispanic; 10 (24%) were Asians and Pacific Islanders. Of 39 patients for whom HBV‐DNA quantification at time of HDV presentation was available, 22 (56%) had undetectable levels; four (10%) had levels > 100 000 IU/mL. Conclusions: HDV affects individuals of all ages and various ethnic groups. Although HBV viral loads are lower, rates of cirrhosis are higher in coinfected patients and higher still in the tri‐infected. Our data support revising screening guidelines to advocate for all patients with HBV to be screened for HDV in order to both give the individual patient important information related to the possible need for treatment and to support the public health goal of reducing transmission by educating HDV‐negative patients about the need for protection against superinfection and HDV‐infected patients about the need to protect against transmission to others.